HPV and p16 expression association with 5-year survival in oral squamous cell carcinoma patients of north-east India - Rajjyoti Das; Rupesh Kumar; Avdhesh Kumar Rai; Anupam Sarma; Lopamudra Kakoti; Amal Chandra Kataki; Mouchumee Bhattacharyya; Manoj Kalita (Advances in Cancer Biology - Metastasis, 2024)
Background: In our study, we examined the 5-year survival of OSCC patients with HPV positive or negative status along with p16 protein expression. Method: A total of 72 biopsy tissue specimens from histologically confirmed oral squamous cell carcinoma (OSCC) patients were collected. HPV detection and genotyping were performed using HPV E6/E7 and HPV- type-specific multiplex primer for nested-PCR. Immunohistochemistry evaluation of pl6 was conducted. SPSS statistical software (ver 20) was used for data analysis. Results: High risk-HPV (hr-HPV) DNA positivity was found in 27.7% (n = 20) of OSCC patients. Stage III OSCC patients were 7.80 times more likely to survive 5 years than stage IV patients (OR-7.80 CI-95%; P-0.03). Among the hr-HPV positive OSCC patients, we found that the median survival time for the 1st year (95%), 3 years (78.5%), and 5 years (38.5%) was significantly higher than that of the hr-HPV negative [1st year (78.6%), 3 years (45.2%) and 5 years (38.5%)] OSCC patients (P-0.03 The survival of male patients with hr-HPV positive OSCC is 9.75 times greater than the survival of patients with HPV negative OSCC (OR-9.75; CI-95%; P-0.05). The p16 expression level (low to overexpression) group and negative P16 expression group of OSCC patients have not demonstrated a significant association with 5-year survival. Conclusion: We conclude that in OSCC cases of North-East India, the presence of hr-HPV in OSCC cases could be a good predictor of 5-year survival rate. Expression of p16 does not appear to have any significant association with 5-year survival.